(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the technological period of current era, many countries observe, the FDI as a boost to their economy. Because of liberalization and FDI policy, India even being late to implement has a better control over foreign investors in her markets. This paper tries to focus on the competitive role of FDI in Indian retail market sector and multi-brand sector. It is also a part of study to analyze the challenges India may face because of the FDI in retail market. The tasks remain which are beyond the scope of this paper are impact of FDI in both market and branding, on Indian Economy.